Risk Factor Classification Effect on Sematok Dam Slopes Stability - Indra Nurtjahjaningtyas; Paksitya Purnama Putra; Sholeh Huda Taufiqurohman (International Association of Lowland Technology, 2021)
The Semantok Dam was built with extreme classified risk factors. These conditions require a more detailed review of its stability with the imposition of Operationing Basic Earthquake (OBE) at the 200-year return period, as well as the imposition of Maximum Design Earthquake (MDE) at the 10000-year return period. This study aimed to determine the response of the dam due to the earthquake load in addition to the influence of pore pressure values under rapid drawdown conditions. Results of analysis using load Maximum Design Earthquake (MDE) of 0.6 g show a significant effect on the slope stability of the dam. In these conditions, there is a failure in maintaining the dam slope stability. Further examination for permanent deformation due to the influence of the earthquake load still meets the required criteria.